Selected aspects of foreign immigration to Poland at the turn of the 20th/21st century. - Długosz, Zbigniew (Bulletin of Geography. Socio-economic Series, 2007)
The aim of this study is to retrace the changes in foreign immigration to Poland in the years 1990–2004. It attempts to provide an assessment of certain, seemingly the most important aspects of immigration to the extent permitted by the data available, such as the size of these influxes and their structure, as well as indicating main directions of such flows of people. The results showed that in recent years the numbers of foreign immigrants to Poland have been growing slightly but steadily.